The impact of electric vehicles and photovoltaic energy integration on distribution network - Talbi, Boutaina; Derri, Mounir; Haidi, Touria; Janyene, Aberrahmane (International Journal of Power Electronics and Drive Systems (IJPEDS), 2024)
The transition towards an eco-friendly and lasting energy system is enabled by the presence of electric vehicles (EVs) and the utilization of renewable energy resources. Despite its intermittent occurrence, solar energy empowers sunny areas to capture renewable energy from sunlight and produce electricity continuously all day long. This energy will be able to smooth the consumption peaks during peak hours and ensure the electrical network flexibility by being injected at various voltage levels. Electric vehicles are supplied by low voltage recharging stations and are seen as power loads that, if rapidly and simultaneously recharged, could potentially affect the stability of the electrical grid. This paper introduces an intelligent method for electric vehicle charging designed to mitigate the impact of simultaneous charging, specifically addressing voltage drop issues. Furthermore, this study demonstrates the positive impact of integrating photovoltaic energy into the distribution network, serving as support, and alleviating the afore cited impact. The simulation results obtained using MATLAB/Simulink illustrate the effectiveness of the proposed strategy in charging electric vehicles, particularly in reducing the observed voltage drop. There is a notable enhancement in voltage drop across all study cases, amounting to a 27 V improvement compared to charging without the proposed method.